2022
DOI: 10.4103/jfmpc.jfmpc_1231_21
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric indices and its association with hypertension among young medical students

Abstract: Introduction: Obesity, defined on the basis of anthropometric measures is a global epidemic and threatening to healthy population worldwide. A research from China among young adults (20--44 years) recorded six and two times the risk of hypertension (HTN) in individuals who were obese and overweight, respectively, relative to normal weight individuals. This study highlights about anthropometric indices and its association with HTN among young medical students at rural medical college. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The study participants' average type II diabetes prevalence was about 61%, and their average blood pressure was about 83%, demonstrating the relationship between metabolic syndrome and asthma. This was discovered to be comparable to other research that established the relationship between asthma and metabolic problems [11,18]. As previously mentioned, insulin resistance impairs the energy production in the mitochondria, which reduces oxygen supply and causes asthma by increasing bronchial reactivity through inhibition of the presynaptic M2 muscarinic receptor and being linked to skeletal muscle weakness, including the respiratory system.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The study participants' average type II diabetes prevalence was about 61%, and their average blood pressure was about 83%, demonstrating the relationship between metabolic syndrome and asthma. This was discovered to be comparable to other research that established the relationship between asthma and metabolic problems [11,18]. As previously mentioned, insulin resistance impairs the energy production in the mitochondria, which reduces oxygen supply and causes asthma by increasing bronchial reactivity through inhibition of the presynaptic M2 muscarinic receptor and being linked to skeletal muscle weakness, including the respiratory system.…”
Section: Discussionsupporting
confidence: 83%
“…Numerous cell types, including vascular endothelial cells, renal epithelial cells, and glandular epithelium, have altered activities in the metabolic syndrome. It is unknown but extremely possible that people with metabolic syndrome have altered airway epithelium or sub-epithelial function [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been concluded from numerous studies that higher BMI is positively associated with prehypertension and hypertension. 8,21 A meta-analysis by Guo et al reported higher body mass indices among individuals with prehypertension. 22 Similar findings were also observed by Parthaje et al in urban adults of South India.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19] Most Linear regression showing neck circumference with components of metabolic syndrome…”
mentioning
confidence: 99%